Considering the issue of potato variety qualifying examination (Solanum tuberosum L.) - А. А. Подгаєцький (Plant Varieties Studying and Protection)
208 potato varieties of domestic and foreign breeding have been examined on Ustymivska examination station of V. Yur’eva plant production Institute UAAS to determine their response during planting material use. By experiment research results was established different variety productivity depending on the origin of plant material and growing in different soil and climatic conditions, applying the special term »zone change growing plant material effect”. As a result of the three-year productivity of different reproduction locations the same varieties potato planting material assessment was founded that in most cases, superiority in performance were varieties that were grown from imported seeds. Experimental studies proved the impact on the productivity expression of physiological aging of the tubers used for planting.